Proceedings of the 2018 Conference on Empirical Methods in Natural Language Processing 2018
DOI: 10.18653/v1/d18-1090
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Essay Scoring Incorporating Rating Schema via Reinforcement Learning

Abstract: Automatic essay scoring (AES) is the task of assigning grades to essays without human interference. Existing systems for AES are typically trained to predict the score of each single essay at a time without considering the rating schema. In order to address this issue, we propose a reinforcement learning framework for essay scoring that incorporates quadratic weighted kappa as guidance to optimize the scoring system. Experiment results on benchmark datasets show the effectiveness of our framework.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…• RL1 Wang et al (2018b) proposed a reinforcement learning based model. In that paper, QWK is used as the reward function, and classification is used to gain the scores.…”
Section: Baselines and Implementation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…• RL1 Wang et al (2018b) proposed a reinforcement learning based model. In that paper, QWK is used as the reward function, and classification is used to gain the scores.…”
Section: Baselines and Implementation Detailsmentioning
confidence: 99%
“…Reinforcement learning based models are also possible solutions. Wang et al (2018b) utilized dilated LSTM to learn text representations.…”
Section: Introductionmentioning
confidence: 99%
“…Our work differs from prior efforts primarily in the particular architecture that we use. Most prior work uses LSTMs (Farag et al, 2018;Wang et al, 2018;Cummins and Rei, 2018) or a combination LSTMs and CNNs (Taghipour and Ng, 2016;Zhang and Litman, 2018), cast as linear or logistic regression problems. In contrast, we use a hierarchically structured model with ordinal regression.…”
Section: Related Workmentioning
confidence: 99%
“…These problems (and the success of deep learning in other areas of language processing) have led to the development of neural methods for automatic essay scoring, moving away from feature engineering. A variety of studies (mostly LSTM-based) have reported AES performance comparable to or better than feature-based models (Taghipour and Ng, 2016;Cummins and Rei, 2018;Wang et al, 2018;Jin et al, 2018;Farag et al, 2018;Zhang and Litman, 2018). However, the current state-of-the-art models still use a combination of neural models and hand-crafted features (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work on automated essay scoring has largely focused on holistic scoring, which summarizes the quality of an essay with a single score (e.g., Taghipour and Ng (2016), Dong et al (2017), Wang et al (2018)). There are at least two reasons for this focus.…”
Section: Introductionmentioning
confidence: 99%